Application of DAST film as organic pyroelectric material and preparation method thereof
By using DAST film and performing annealing and polarization treatment, the problem of low pyroelectric coefficient of existing organic pyroelectric materials is solved, and high pyroelectric coefficient and excellent pyroelectric properties are achieved, which is suitable for the application of pyroelectric devices.
Patent Information
- Application Number
- CN202310166576.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-02-27
AI Technical Summary
The pyroelectric coefficient of existing organic pyroelectric materials is low, which limits its wide application in pyroelectric devices.
DAST (4-(4-dimethylaminostyrene)methylpyridine p-toluenesulfonate) film was prepared by combining spin coating and spray coating, and annealing and polarization were performed to improve the pyroelectric performance.
The pyroelectric coefficient of the DAST film was significantly improved to reach 33.18μC/m2·K, which was better than other single-component organic pyroelectric materials, and overcome the shortcomings of single crystal materials in terms of size, thickness, etc.
Smart Images

Figure CN116621468B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field related to pyroelectric materials, and specifically provides an application of a DAST (4-(4-dimethylaminophenylvinyl)methylpyridine toluenesulfonate) film as an organic pyroelectric material and a preparation method thereof. Background Art
[0002] As an important subclass of piezoelectric materials, pyroelectric materials have attracted more and more attention due to their unique pyroelectric effect caused by spontaneous polarization, and are widely used in pyroelectric sensors, detectors, actuators and other devices; and with the rapid development of the Internet of Things and the advancement of device miniaturization, pyroelectric materials have developed from traditional sensors and detectors to new wearable, self-powered, convenient and portable pyroelectric devices; along with this development trend, people have an increasingly strong demand for pyroelectric materials with low cost, light weight, environmental friendliness and high biocompatibility.
[0003] Traditional inorganic pyroelectric materials have advantages such as high pyroelectric coefficient, such as lithium tantalate (LiTaO3), lead titanate (PbTiO3), and lead zirconate titanate (PZT). However, such materials usually have disadvantages such as being thick, hard, brittle, and requiring harsh preparation conditions. In particular, some inorganic pyroelectric materials contain elements that are not environmentally friendly, such as lead-containing PZT and lithium-containing lithium niobate, which limits the application of related materials in wearable, biocompatible devices, etc. (see S. Uma, J. Philip, Pyroelectric and Thermal, AIP Conference Proceedings. American Institute of Physics, 2011, 1349(1): 349-350.). In comparison, organic pyroelectric materials have the advantages of simple preparation, no need for high temperature environment, low price, soft performance, good biocompatibility, etc. They are easy to make into thin films of any shape and large area, and are widely used in energy collection, gas detection and other applications (see A. Batra, A. Almuatasim, and B. David, Abstracts 230. No. 1. The Electrochemical Society, 2016 Inc.). The shortcomings of surface inorganic materials can be overcome by organic materials; however, the pyroelectric coefficient of organic pyroelectric materials is usually more than one order of magnitude lower than that of inorganic pyroelectric materials, which limits the wide application of organic pyroelectric materials. Therefore, finding organic pyroelectric materials with excellent performance is a difficulty that needs to be overcome in this field. Summary of the invention
[0004] The purpose of the present invention is to use a DAST (4-(4-dimethylaminophenylvinyl)methylpyridine toluenesulfonate) film as an organic pyroelectric material and a preparation method thereof, so as to improve the pyroelectric coefficient of the organic pyroelectric material. The present invention adopts a method combining spin coating and spray coating to prepare the DAST organic film. After annealing and polarization treatment, the DAST film uses the high non-central symmetry of the DAST molecule to obtain a large pyroelectric current, thereby converting the thermal energy in the environment into electrical energy, and realizing the application of the DAST organic film as an organic pyroelectric material; compared with traditional inorganic pyroelectric materials, the DAST film as an organic pyroelectric material has the advantages of flexibility, environmental protection, simple process, low price, etc. In addition to being used in devices such as sensors, detectors, and actuators, it can also be used in the fields of biocompatibility and wearable devices.
[0005] To achieve the above object, the technical solution adopted by the present invention is:
[0006] The application of DAST film as an organic pyroelectric material is characterized in that the DAST film is prepared on the upper surface of the ITO layer of ITO glass, and a conductive layer is deposited on the upper surface of the DAST film, and the DAST organic film is sequentially annealed and polarized; the conductive layer serves as the upper electrode and the ITO layer serves as the lower electrode. Under the action of temperature changes, the DAST film will generate induced charges on the surface electrodes (upper electrode and lower electrode), convert thermal energy into electrical energy, and generate pyroelectric current.
[0007] Furthermore, the thickness of the DAST film is 2 to 50 μm.
[0008] Furthermore, the conductive layer is an electrode composed of one or more of aluminum, gold, titanium, titanium nitride, titanium silicide, titanium tungsten alloy, tungsten, tungsten silicide, tungsten nitride, nickel, nickel silicide, nickel nitride, tantalum, tantalum nitride, iron, platinum, copper, silver, chromium and nickel-chromium alloy.
[0009] Furthermore, the thickness of the conductive layer is 10 to 500 nm.
[0010] Furthermore, the method for preparing the DAST film comprises the following steps:
[0011] Step 1. Add an organic solvent to a certain amount of DAST powder, and place the solution in an ultrasonic machine for ultrasonication until the DAST powder is completely dissolved to obtain a uniform DAST organic solution, wherein the concentration of DAST is 1wt%;
[0012] Step 2. Use an ITO glass sheet as a substrate and clean it for later use;
[0013] Step 3. The DAST organic solution is simultaneously coated on the upper surface of the ITO layer by a combination of spin coating and spray coating, and the coating is repeated 5 to 20 times; the specific coating process is: the spin coater is used to rotate at a speed of 500 to 1500 rpm and 2500 to 3500 rpm for 30 to 120 seconds respectively; at the same time, during the spin coating process, the spraying is performed in an atmospheric environment at a pressure of 0.1 to 0.5 MPa and with high-purity nitrogen as a carrier gas;
[0014] Step 4. Place the substrate with the DAST film in a drying oven for annealing, the drying oven temperature is 20-200° C., the annealing atmosphere is air, argon, neon, helium, nitrogen or vacuum, and the annealing time is 100-200 min;
[0015] Step 5. Depositing a conductive layer on the upper surface of the DAST film;
[0016] Step 6. Polarize the DAST film.
[0017] Furthermore, in step 1, the organic solvent is one of isobutanol, butanol, pentanol, methanol, water, ethanol, propanol, isobutanol, butanol, pentanol, dimethylformamide, dimethyl sulfoxide, acetonitrile or methyl chloride, or a mixture of several of them.
[0018] Furthermore, in step 1, the ultrasonic time is not less than 3 hours.
[0019] Furthermore, in step 2, the cleaning process of the ITO glass sheet is as follows: first, the glass sheet is cleaned with a detergent to remove surface impurities, and then rinsed with deionized water; then, ultrasonically cleaned with acetone, anhydrous ethanol and deionized water in sequence; finally, blown dry with nitrogen.
[0020] Furthermore, in step 5, the conductive layer is deposited on the upper surface of the DAST film by using one or more of magnetron sputtering, thermal evaporation, pulsed laser deposition, and chemical vapor deposition.
[0021] Furthermore, in step 6, the polarization method is one of oil bath polarization, thermal polarization, corona polarization, plasma polarization, and AC / DC polarization.
[0022] Furthermore, in step 6, the polarization temperature is 50-150° C., the polarization voltage is 200-1200 V, and the polarization time is 1-20 h.
[0023] In terms of working principle:
[0024] As a piezoelectric material, the monoclinic phase of 4-(4-dimethylaminophenylvinyl)methylpyridine toluenesulfonate (DAST) single crystals gives it excellent piezoelectric properties, but the growth period of high-quality DAST single crystals is long, and the thickness and size of the single crystals are uncontrollable, and the sizes of the grown single crystals vary. On this basis, the present invention finds through analysis that DAST is an organic molecular salt composed of anions and cations. The strong Coulomb force between molecules makes the DAST conjugated molecules present a non-centrosymmetric structure. This property can be used to achieve excellent pyroelectric performance; therefore, the present invention proposes a method combining spin coating and spray coating to prepare DAST organic thin film, anneal and polarize the thin film, and use it as an organic pyroelectric material. Under the action of temperature changes, the DAST thin film will generate induced charges on the surface electrodes, convert thermal energy into electrical energy, and generate a large pyroelectric current; through test calculations, it is obtained that the DAST thin film organic pyroelectric material provided by the present invention can achieve a pyroelectric coefficient of 33.18μC / m 2 ·K, which is significantly better than other single-component organic pyroelectric materials; and, DAST thin films can overcome the shortcomings of single-crystal materials in terms of size and thickness, thereby realizing the application of DAST in pyroelectric devices.
[0025] In summary, the beneficial effects of the present invention are:
[0026] 1) The present invention successfully prepares DAST organic thin film by combining spin coating and spray coating, and applies it as an organic pyroelectric material for the first time. A sinusoidal temperature wave is given to the DAST organic thin film pyroelectric material, and the DAST organic thin film generates a cosine-varying pyroelectric current, converting thermal energy into electrical energy. The DAST organic thin film pyroelectric material in the present invention has a larger pyroelectric current and a higher pyroelectric coefficient, which is significantly better than other single-component organic pyroelectric materials.
[0027] 2) The DAST organic pyroelectric film of the present invention has a simple preparation process, environmentally friendly materials, low price, does not require high-temperature preparation, and has low production cost; and avoids the problems of long growth cycle, difficult size control, and fragility of DAST single crystals.
[0028] 3) The DAST organic pyroelectric film of the present invention has the advantages of flexibility, environmental protection, simple process, low price, etc., and can be used in devices such as sensors, detectors, actuators, and can also be used in the fields of biocompatibility, wearable devices, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a schematic diagram of the application structure of the DAST film as an organic pyroelectric material in the present invention.
[0030] Figure 2 Schematic diagram of the pyroelectric current test system.
[0031] Figure 3 It is the pyroelectric current of the DAST organic thin film pyroelectric material in the embodiment of the present invention when annealed at 120°C.
[0032] Figure 4 It is the pyroelectric current of the DAST organic thin film pyroelectric material in the embodiment of the present invention when annealed at 160°C. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below with reference to the accompanying drawings and embodiments.
[0034] This embodiment provides an application of a DAST film as an organic pyroelectric material, such as Figure 1 As shown, the DAST film 3 is prepared on the upper surface of the ITO layer of the ITO glass composed of a glass substrate 1 and an ITO layer 2, and is annealed and polarized, and a conductive layer 4 is deposited on the upper surface of the DAST film; the conductive layer serves as an upper electrode and the ITO layer serves as a lower electrode, and the two are respectively led out through a wire 5; under the action of temperature changes, the DAST film will generate induced charges on the surface electrodes (upper electrode and lower electrode), convert thermal energy into electrical energy, and generate pyroelectric current.
[0035] The above structure is prepared by the following steps:
[0036] Step 1. Prepare DAST organic solution: add 5 ml of methanol solvent to 40 mg of DAST powder, and ultrasonicate the solution in an ultrasonic machine until DAST is completely dissolved in methanol; usually, the ultrasonication time is not less than 3 hours, and finally a uniform DAST methanol solution is obtained;
[0037] Step 2. Select an area of 2×2cm 2 The ITO glass sheet was used as a substrate. First, the ITO glass sheet was cleaned with detergent to remove surface impurities, and then rinsed with deionized water; then, acetone, anhydrous ethanol and deionized water were used for ultrasonic cleaning for 15 minutes in sequence; finally, it was blown dry with nitrogen and set aside;
[0038] Step 3. On the cleaned ITO glass substrate, the DAST methanol solution was spin-coated at a speed of 1000 rpm and 3000 rpm for 60 seconds respectively using a spin coater; at the same time, the DAST methanol solution was evenly sprayed in an atmospheric environment at a pressure of 0.3 MPa and with high-purity nitrogen as a carrier gas; the process was repeated 10 times to prepare a DAST film with a thickness of 25 μm on the ITO glass substrate;
[0039] Step 4. placing the ITO glass substrate with the DAST film in an oven, and annealing it at 160° C. for 2 hours in an air environment to obtain an annealed DAST organic film;
[0040] Step 5. Use thermal evaporation to deposit a 200nm thick Al metal film on the upper surface of the DAST organic film as the upper electrode, and use conductive silver paste to lead out the copper wire; then use conductive tape to stick the copper wire to the ITO surface of the ITO glass as the lower electrode; thus, the DAST organic thin film pyroelectric material is prepared.
[0041] Step 6. The DAST organic film obtained in step 5 is polarized by a thermal polarization method. The specific polarization conditions include: applying a polarization voltage of 600 V at a polarization temperature of 80° C. and a polarization time of 5 hours.
[0042] Use Figure 2 The pyroelectric current test system shown in FIG. 1 is used to test the above structure. The pyroelectric current of the organic thin film pyroelectric material of this embodiment is polarized at 80°C and 600V for 5 hours and annealed at 120°C for 2 hours. Figure 3 As shown in the figure, the pyroelectric current of the DAST film is 5.25nA, and the corresponding pyroelectric coefficient is 13.47μC / m 2 ·K; It can be seen that the present invention is the first to test the pyroelectric properties of DAST organic materials. The measured pyroelectric coefficient of the pure DAST film (13.47μC / m 2 K) is significantly higher than polyvinyl chloride (PVC) (1μC / m 2 ·K), polyacrylonitrile (PAN) (1μC / m 2 ·K), polyacrylamide (PAA) (1μC / m 2 ·K), polyamide 11 (3μC / m 2 ·K) and other single-component organic pyroelectric materials.
[0043] Use Figure 2 The pyroelectric current test system shown in FIG. 1 is used to test the above structure. The pyroelectric current of the organic thin film pyroelectric material of this embodiment is polarized at 80°C and 600V for 5 hours and annealed at 160°C for 2 hours. Figure 4 As shown in the figure, the pyroelectric current of the DAST film is 12.93nA, and the corresponding pyroelectric coefficient is 33.18μC / m 2 ·K; It can be seen that the measured pyroelectric coefficient of the pure DAST film (33.18μC / m 2 K) is significantly higher than that of reported single-component organic pyroelectric materials, such as PVF2 (24 μC / m 2K), PVDF (27μC / m 2 ·K), polyurea (4.3μC / m 2 It is worth mentioning that the pyroelectric coefficient of the pure DAST film (33.18μC / m 2 K) is close to that of PVDF-based composite materials, such as P(VDF-TrFE) composite membrane (43μC / m 2 K), PT / P (VDF-TrFE) composite membrane (62μC / m 2 ·K). Therefore, increasing the annealing temperature can make DAST organic thin film obtain better pyroelectric performance. Compared with existing inorganic pyroelectric materials, DAST organic thin film pyroelectric materials have the advantages of flexibility, environmental protection, simple process, low price, etc., overcome the shortcomings of single crystal materials in external electric field, size, thickness, etc., and can be widely used in pyroelectric sensors, detectors, actuators and other devices.
[0044] The above description is only a specific implementation mode of the present invention. Any feature disclosed in this specification, unless otherwise stated, can be replaced by other alternative features that are equivalent or have similar purposes; all the disclosed features, or all the steps in the methods or processes, except for mutually exclusive features and / or steps, can be combined in any way.
Claims
1. Application of DAST film as organic pyroelectric material, characterized in that: The DAST (4-(4-dimethylaminophenylvinyl)methylpyridine p-toluenesulfonate) film is prepared on the upper surface of the ITO layer of the ITO glass, and the preparation process is as follows: a DAST organic solution is simultaneously coated on the upper surface of the ITO layer by a combination of spin coating and spray coating to form a DAST organic film, and the DAST organic film is annealed and polarized, and the annealing temperature is 120-200° C.; a conductive layer is deposited on the upper surface of the DAST film, the conductive layer serves as an upper electrode, and the ITO layer serves as a lower electrode. Under the action of temperature changes, the DAST film generates induced charges on the surface electrode, converts thermal energy into electrical energy, and generates pyroelectric current.
2. The use of the DAST film as an organic pyroelectric material according to claim 1, characterized in that: The thickness of the DAST film is 2-50 μm.
3. The use of the DAST film as an organic pyroelectric material according to claim 1, characterized in that: The conductive layer is an electrode composed of one or more of aluminum, gold, titanium, titanium nitride, titanium silicide, titanium tungsten alloy, tungsten, tungsten silicide, tungsten nitride, nickel, nickel silicide, nickel nitride, tantalum, tantalum nitride, iron, platinum, copper, silver, chromium and nickel-chromium alloy.
4. The use of the DAST film as an organic pyroelectric material according to claim 1, characterized in that: The thickness of the conductive layer is 10-500 nm.
5. The use of the DAST film as an organic pyroelectric material according to claim 1, characterized in that: The method for preparing the DAST film comprises the following steps: Step 1. Add an organic solvent to a certain amount of DAST powder, and place the solution in an ultrasonic machine for ultrasonication until the DAST powder is completely dissolved to obtain a uniform DAST organic solution, wherein the DAST concentration is 1 wt%; Step 2. Use an ITO glass sheet as a substrate and clean it for later use; Step 3. The DAST organic solution is simultaneously coated on the upper surface of the ITO layer by a combination of spin coating and spray coating, and the coating is repeated 5 to 20 times; the specific coating process is: the spin coater is used to rotate at a speed of 500 to 1500 rpm and 2500 to 3500 rpm for 30 to 120 seconds respectively; at the same time, during the spin coating process, the spraying is performed in an atmospheric environment at a pressure of 0.1 to 0.5 MPa and with high-purity nitrogen as a carrier gas; Step 4. Place the substrate with the DAST film in a drying oven for annealing, the drying oven temperature is 120-200° C., the annealing atmosphere is air, argon, neon, helium, nitrogen or vacuum, and the annealing time is 100-200 min; Step 5. Depositing a conductive layer on the upper surface of the DAST film; Step 6. Polarize the DAST film.
6. Use of the DAST film as an organic pyroelectric material according to claim 5, characterized in that: In step 1, the organic solvent is one of isobutanol, butanol, pentanol, methanol, ethanol, propanol, dimethylformamide, dimethyl sulfoxide, acetonitrile or methyl chloride, or a mixture of several of them.
7. The use of the DAST film as an organic pyroelectric material according to claim 5, characterized in that: In step 1, the ultrasonication time is not less than 3 hours.
8. The use of the DAST film as an organic pyroelectric material according to claim 5, characterized in that: In step 2, the cleaning process of the ITO glass sheet is as follows: first, the glass sheet is cleaned with a detergent to remove surface impurities, and then rinsed with deionized water; then, ultrasonic cleaning is performed using acetone, anhydrous ethanol and deionized water in sequence; finally, it is blown dry with nitrogen.
9. The use of the DAST film as an organic pyroelectric material according to claim 5, characterized in that: The conductive layer is deposited on the upper surface of the DAST film by using one or more of magnetron sputtering, thermal evaporation, pulsed laser deposition, and chemical vapor deposition methods.
10. The use of the DAST film as an organic pyroelectric material according to claim 5, characterized in that: In step 6, the polarization method is one of oil bath polarization, thermal polarization, corona polarization, plasma polarization, AC / DC polarization, and the polarization temperature is 50-150 o C. Polarization voltage is 200~1200V and polarization time is 1~20h.
Citation Information
Patent Citations
DAST-carbon nano tube composite film and preparation method thereof
CN102794947A
DAST flexible composite piezoelectric material and preparation method therefor
CN106876577A